PEMANFAATAN BAHAN LIMBAH PLASTIK PADA PEMBELAJARAN KOLASE UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS IV DI UPTD SD NEGERI 10 JULI KABUPATEN BIREUEN - Amanda, Raisa; Fitri, Aida; Hasniyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Creativity is one of the important abilities that need to be developed in elementary school students, especially in fine arts learning to help students express ideas and develop creative thinking skills. However, in practice, art learning still does not utilize materials in the surrounding environment as meaningful learning media so that student engagement in the learning process is not optimal. Initial conditions indicate that student creativity is relatively low, where 62% of students have not reached the Learning Objective Achievement Criteria (KKTP) of 70. This study aims to describe the process of utilizing plastic waste materials in collage learning and increasing the creativity of fourth-grade students of UPTD SD Negeri 10 Juli, Bireuen Regency. This study uses a qualitative approach with a descriptive research type. The research subjects were 21 fourth-grade students. Data collection techniques were carried out through observation and student performance tests. Data analysis techniques used the Miles, Huberman, and Saldana models which include data reduction, data presentation, and conclusion drawing. The results of the study indicate that the use of plastic waste materials in collage learning can be implemented effectively through the stages of material preparation, the manufacturing process, and the completion of the work. Student creativity increased, as indicated by the percentages for each indicator: fluency (91.6%), flexibility (86.9%), originality (83.3%), and elaboration (78.5%), with an overall average of 85.1%, which is in the very good category. Therefore, it can be concluded that the use of plastic waste materials in collage learning can enhance the creativity of fourth-grade students and provide an engaging, active, and meaningful learning experience.